What are the outcomes of marine site protection on poverty of coastal communities in Southeast Asia? A systematic review protocol - Mohd Aizat Zain; Julia Suhaimi; Maznah Dahlui; Hong Ching Goh; Amy Yee-Hui Then; Nur Asyikin Yakub; Mohd Iqbal Mohd Noor; Ruth Garside; Jacqualyn Eales; Edgar Jose; Fatimah Kari (Environmental Evidence, 2022)
Abstract Background Many conservation management interventions have been set up to bring win–win outcomes for both biodiversity conservation and the well-being of the local communities. Nevertheless, the implementation process of marine protected areas (MPAs) can generate unexpected outcomes and fail to reach its objectives in addressing communities’ challenges. Therefore, it is crucial to have a better understanding of how MPAs influence the socioeconomic aspects of the coastal communities. This paper describes the protocol to conduct a systematic review which aims to explore and review the evidence that reflects the outcomes of marine site protection on poverty reduction in terms of economic and material living standards among the coastal communities in Southeast Asia. The review question is “What are the outcomes of marine site protection implementation on poverty in terms of material and economic living standards of coastal communities in Southeast Asia?”. Methods The systematic review uses rigorous search strategies and selection methods based on pre-defined eligibility criteria to identify and examine published journal articles and grey literature that are available on the review topic. Relevant studies and grey literature will be extracted from a recent systematic map of the evidence documenting the effect of marine or coastal nature conservation or natural resource management activities on human well-being in Southeast Asia. We will search online databases including Web of Science Core Collection, Ovid Medline®, Environmental Complete, Scopus, as well as Google Scholar and sources of grey literature for any additional literature available since the evidence map was created. For this review, the populations of interest are from coastal communities in the Southeast Asia region. Comparators to marine site protection will be no intervention and/or pre-MPA implementation. The economic and material living standards, which are the poverty domains, will be evaluated as outcomes. Once we have identified relevant literature, we will perform a critical appraisal, data extraction, and synthesis appropriate to the type of literature found, to investigate the effect of marine site protection on poverty reduction.